STUDY OF CHEMICAL COMPOSITION AND PHYTOCHEMICAL COMPOUNDS OF LOCAL OLIVE (OLEA EUROPAEA L.) LEAVES - Wed Fathi Ibrahim,; Ahmed Chaloob Saddam,; Terezie Tolar-Peterson, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
The current study aimed to estimate the chemical composition and detect bioactive compounds, such as polyphenols and flavonoids, in the aqueous and alcoholic extracts of olive leaves. The study involved collecting olive leaves from areas in Al Za'franiya, Baghdad, Iraq. According to the chemical composition, olive leaves have a good protein content (9.89%), which may play a major role in alleviating global malnutrition. The results revealed that the leaves contain high total Ash (22.20%), carbohydrates (55.66%), energy (273.52 kcal/100g), and low total fat content (1.28%). Ethanol extract 70% contained the highest concentration of oleuropein (298.0 mg/L), which is responsible for antioxidant and pharmacological potential, as well as enhancing the immune system. The study concluded that olive leaves represent a rich and diverse natural source of active compounds, which opens horizons for their use in the food and health industries.